How Nursing Ethics as a Subject Changes: An analysis of the first 11 years of publication of the journal Nursing Ethics - Tschudin, Verena (Nursing ethics, 2006)
By analysing the first, second, 10th and 11th years of publication (i.e. volumes 1, 2, 10, 11) of Nursing Ethics, I will show the significant visible trends in the articles and draw some conclusions. The trends are visible at various levels: from simple analysis of an issue, or a comment on a situation in the early years, to in-depth philosophical and research studies; and from short statements to much longer articles. The ethical approaches used go from either none or unquestioned assumptions to several approaches used in any one study. This corresponds to the general postmodern trend in society. The interpretation made of these trends is of a kind of protest at nurses and nursing being devalued. Although this is expressed negatively, the positive message conveyed is that nurses are now taking their professional life into their own hands, vigorously and more daringly than a decade ago.